2012
DOI: 10.17221/187/2011-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed gene transcripts in wheat and barley leaves upon leaf spot infection

Abstract: A cDNA library was created on the basis of transcripts that were generated during the process of infection of wheat and barley with Pyrenophora tritici-repentis or P. teres. Due to the time course of infection assays, the leaves were collected at various intervals after inoculation until 100 h after inoculation. We compared the temporal development of the two pathogens, as well as the effect of varieties of the same crop species, and differences among isolates of a single pathogen. The appressoria and vesicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Global gene expression experiments showed that numerous defence‐related genes were induced upon P. tritici‐repentis infection and ToxA treatment in wheat seedlings prior to symptom appearance; and that sensitive genotypes had more pronounced responses (i.e. hypersensitivity response as a result of loss of coordination) due to hijacking of the host's innate immunity, as compared to insensitive genotypes, highlighting the evidence of overlapping mechanisms associated with effector‐triggered immunity (ETI) and effector‐triggered susceptibility (ETS) (Adhikari et al ., ; Dumalasová et al ., ; Pandelova et al ., ). This may explain the enhanced level of resistance, induced or expressed at later developmental adult growth stages due to prior infection at an earlier stage, observed for the accessions exhibiting APR in the integrated experiment under CEC.…”
Section: Discussionmentioning
confidence: 97%
“…Global gene expression experiments showed that numerous defence‐related genes were induced upon P. tritici‐repentis infection and ToxA treatment in wheat seedlings prior to symptom appearance; and that sensitive genotypes had more pronounced responses (i.e. hypersensitivity response as a result of loss of coordination) due to hijacking of the host's innate immunity, as compared to insensitive genotypes, highlighting the evidence of overlapping mechanisms associated with effector‐triggered immunity (ETI) and effector‐triggered susceptibility (ETS) (Adhikari et al ., ; Dumalasová et al ., ; Pandelova et al ., ). This may explain the enhanced level of resistance, induced or expressed at later developmental adult growth stages due to prior infection at an earlier stage, observed for the accessions exhibiting APR in the integrated experiment under CEC.…”
Section: Discussionmentioning
confidence: 97%
“…Barley plants are affected by the presence of several types of foliar pathogenic fungi, such as Ramularia collo-cygni, Pyrenophora teres, Cochliobolus sativus, Puccinia hordei and Rhynchosporium secalis, which are responsible for causing diseases (Carretero et al, 2015;Romero et al, 2020). In fact, net blotch (NB) caused by P. teres (anamorph Drechslera teres) can induce yield losses greater than 50% in barley (Statkeviciute et al, 2010;McLean and Hollaway, 2018) due to a reduction in the number of kernels per spike, grain size, and total photosynthetic leaf area (Dumalasová et al, 2012). In template regions, high rainfall (between 153 and 154 mm) aggravates the damage caused by NB (Steffenson and Webster, 1992;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…NB has two forms differentiated by the symptoms: net form (NFNB) and spot form (SFNB). NFNB, caused by P. teres f. teres, induces horizontal and vertical crisscrossed dark brown venation on barley leaves that can become chlorotic (Dumalasová et al, 2012), whereas SFNB, caused by P. teres f. maculata, produces circular or elliptical dark brown spots surrounded by chlorotic leaf tissue (Carlsen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations